Heart Rate Variability Analysis in Congestive Heart Failure: The Need for Standardized Assessment Protocols - Míková, Monika; Pospíšil, David; Řehoř, Jan; Malik, Marek (Reviews in cardiovascular medicine, 2025)
Heart rate variability (HRV) analysis is a noninvasive tool that allows cardiac autonomic control to be assessed. Numerous studies have reported HRV measurements, related changes, and clinical implications for heart failure patients. This review evaluates HRV characteristics in congestive heart failure (CHF), focusing on different recording durations and the diagnostic and prognostic values using HRV measurements. The recording durations are classified as (a) ultra short-term (substantially shorter than 5 minutes), (b) short-term (5 minutes), and (c) long-term (nominal 24 hours). This review of HRV diagnostic and prognostic significance in CHF focuses on time- and frequency-domain HRV measures that have previously been extensively studied. Reported studies document that HRV is lowered in CHF patients, whereas HRV increases may indicate disease improvement, e.g., in CHF patients undergoing cardiac resynchronization therapy. Reduced HRV has consistently been found to be associated with all-cause mortality in CHF patients. However, different thresholds of long-term HRV indices have been proposed as mortality predictors; meanwhile, findings related to the prediction of other cardiac events, including sudden cardiac death, remain inconsistent. HRV is reduced in CHF patients, but the use of HRV as a risk factor remains controversial, with no established cut-off values. HRV does not provide a clinically useful prediction of sudden cardiac death or other cardiac events in CHF patients. Thus, we advocate standardization of investigative protocols based on the existing time- and frequency-domain HRV indices rather than further developing more complex methods. Short-term recordings are preferable for clinical application and measurement reproducibility; thus, future investigations should focus on the following key questions: 1. How to design standardized short HRV tests suitable for outpatient settings? 2. Which HRV indices should be preferred, and what are their optimal prognostic thresholds? 3. How to standardize HRV assessment conditions to minimize external influences?
Keywords: spectral analysis; heart rate variability; congestive heart failure; risk prediction; time-domain methods